1993
DOI: 10.2307/972136
|View full text |Cite
|
Sign up to set email alerts
|

Tecoh, Izamal: Nobleza Indigena y Conquista Española

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…In contrast to more peripheral houses, centrally located residences at the sites of Tecoh and Ek’ Balam were situated close to features apparently used for the production of indigo and lime for plaster (Hanson, 2008; Millet Cámara, Ojeda Mas, and Suárez Aguilar, 1993). These finds suggest that elite site residents adopted new technologies for their economic benefit.…”
Section: Manifestations Of Violence In the Countrysidementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to more peripheral houses, centrally located residences at the sites of Tecoh and Ek’ Balam were situated close to features apparently used for the production of indigo and lime for plaster (Hanson, 2008; Millet Cámara, Ojeda Mas, and Suárez Aguilar, 1993). These finds suggest that elite site residents adopted new technologies for their economic benefit.…”
Section: Manifestations Of Violence In the Countrysidementioning
confidence: 99%
“…Evidence for survivance from initial research at Tahcabo includes the early‐colonial hunting and mobility mentioned above (and seen also at the outskirts of the nearby site of Ek’ Balam; Hanson, 2008, 1324–29), and late‐colonial community‐wide food‐sharing activities and strategies for economic diversification that included care for plants and animals, craft activities such as embroidery, and wage labor (Dedrick, 2019). Scholars working elsewhere have demonstrated that residents of rural Yucatán experimented with and adopted introduced plants, animals, and technologies (such as water‐drawing features and production facilities) in heterogeneous ways based on social standing and other factors as they pursued resilient livelihood strategies (Alexander and Hernández Álvarez, 2018; Alexander and Williams, 2019; deFrance and Hanson, 2008; Hanson, 2008; Hoil Gutiérrez, 2010; Millet Cámara, Ojeda Mas, and Suárez Aguilar, 1993). Eventually, perhaps after initial farming restrictions subsided, rejolladas became key places for horticultural experimentation (Dedrick et al., 2020, 13; Hoil Gutiérrez, 2010, 103).…”
Section: Manifestations Of Violence In the Countrysidementioning
confidence: 99%
“…Estos trabajos iniciales fueron completados durante la campaña de 1992 centrada en la restauración de la iglesia y la finalización del levantamiento topográfico de la parte central del sitio (Figura 2). Como resultado de ello, contamos con una planimetría de 14 ha, en la que pueden identificarse seis estructuras correspondientes al período colonial (Figura 2), así como un reducido registro cerámico (concretamente seis sondeos) en los que se constató la presencia de materiales correspondientes a los períodos clásico, postclásico, y colonial (Millet Cámara y Burgos Villanueva 1992, 1994Millet Cámara et al 1993).…”
Section: Primeros Trabajos De Campounclassified
“…Casos conocidos son, por ejemplo, Dzibilchaltun en el estado de Yucatán (Folan 1970) y Osumacinta en el estado de Chiapas (Beristain 1984(Beristain , 1996. La presencia de siete construcciones de características afines parece ser prueba evidente de la validez de una hipótesis centrada en la posible existencia de una nobleza indígena que, a cambio de su fidelidad y colaboración con las autoridades españolas recibiría un trato especial, materializado, tanto en su relevancia en la política local, como en el disfrute de espacios y elementos de cultura material diferentes a los del resto de la población (Millet Cámara et al 1993). 3 En dos asentamientos coloniales del área beliceña se ha constatado también la existencia de construcciones de características similares a las de Tecoh.…”
Section: Características Constructivas Y Patrón De Asentamientounclassified